The parent-child unmanned air vehicle concept study - Nochahrli, Tarek Sami, 1976- (Massachusetts Institute of Technology, 1999)
Thesis (M.Eng.)--Massachusetts Institute of Technology, Dept. of Aeronautics and Astronautics, 1999. Includes bibliographical references (p. 92). The Parent Child Unmanned Aerial Vehicle (PCUAV) concept was developed within the context of the MIT Draper Technology Development Partnership Project. A desire at Draper Laboratory to build a fixed wing surveillance airplane to enhance the capabilities of its unmanned vehicle fleet initiated the project. The development objectives included the design of a first-of-a-kind system to be completed in two years (having started in June 1998), and the stimulation of the entrepreneurial spirit of involved engineering students at MIT. A conceptual design derived after eleven months of research includes a system of vehicles where the parent vehicle (acting as a transport vehicle) has the capability of carrying mini and micro unmanned vehicles, deploying them at a mission site, and relaying the collected data by those vehicles back to the ground station. This thesis describes the stages followed during the design process and shows the results of several studies that can be used for the selection of an appropriate demonstration concept. by Tarek Sami Nochahrli. M.Eng.